Dye‐Sensitized Solar Cells: Design‐to‐Device Approach Affords Panchromatic Co‐Sensitized Solar Cells (Adv. Energy Mater. 5/2019). Issue 5 (1st February 2019) - Cooper, Christopher B.; Beard, Edward J.; Vázquez‐Mayagoitia, Álvaro; Stan, Liliana; Stenning, Gavin B. G.; Nye, Daniel W.; Vigil, Julian A.; Tomar, Tina; Jia, Jingwen; Bodedla, Govardhana B.; Chen, Song; Gallego, Lucía; et al.
Abstract : In article number, 1802820, by Jacqueline M. Cole and co‐workers, a 'design‐to‐device' strategy is employed to systematically engineer panchromatic optical absorption for dye‐sensitized solar cell applications. The cover shows how a series of algorithmically encoded forms of structure‐property relationships act as molecular engineering machinery to sift through 9431 chemicals, until a few reach the 'winning platform'; these predictions are experimentally validated. Image designed by Helen Towrie (STFC).